Elucidating the roles of annexin-like molecules in the protozoan parasite giardia intestinalis: an approach to the control of giardiasis - Candy, Chuah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
Giardiasis is a disease caused by protozoan parasite Giardia intestinalis. Herein, we sought to examine the role of alpha-giardins in response to hydrogen peroxide (H202) treatment in G. intestinalis. Results showed that Giard1a treated with increased concentration of H20 2 demonstrated significant reduction in cell viability and significant increase reactive oxygen species production. We found that alpha-2 and alpha-3 giardin showed significant up-regulated transcriptional expression in H,O,-treated Giardia at 1 h time-point, whereas gene expression level of alpha-7.2 and alpha-7.3 giardin up-regulated significantly at 4h time-point Alpha-11 giardin demonstrated up-regulated gene expression at a later time-point (8h and 24h) in H,02- treated Giardia. Together these findings suggest that alpha giardins could serve as potential promising target for future drug design and vaccine development